Thyroid disease and hypothyroidism are associated with poor COVID-19 outcomes: A systematic review, meta-analysis, and meta-regression. Issue 6 (November 2021) - Damara, Fachreza Aryo; Muchamad, Galih Ricci; Ikhsani, Rizkania; Hendro; Syafiyah, Anisa Hana; Bashari, Muhammad Hasan
Abstract: Background and aims: Coronavirus disease (COVID-19) still becomes a global burden that affected people in different groups. The aim of this study was to evaluate the association between thyroid disease and the outcome of COVID-19 patients. Method: This was a meta-analysis study from articles obtained through a systematic literature search to investigate the relationship between thyroid disease and COVID-19 outcomes. Composite poor outcomes comprised of severity, mortality, intensive care unit (ICU) admission, and hospitalization. Results: A total of 31339 patients from 21 studies included in this study. Thyroid disorder was associated with increased composite poor outcome (risk ratio (RR) 1.87 [95% confidence interval (CI) 1.53, 2.27], p < 0.001; I2 = 84%, p < 0.01), this included higher disease severity (RR 1.92 [1.40, 2.63], p < 0.05; I2 = 86%, p < 0.01), ICU admission (RR 1.61 [1.12, 2.32], p > 0.05; I2 = 32%, p < 0.05), mortality (RR 2.43 [1.44, 4.13], p < 0.05; I2 = 83%, p < 0.01), and hospitalization (RR 1.28 [1.17, 1.39], p < 0.05; I2 = 0%, p < 0.96). Meta-regression analysis indicated that age (p = 0.002) was a significant influence that affects the association. Also, the presence of unspecified thyroid disease (RR 1.91 [1.38, 2.65], p < 0.05; I2 = 81%, p < 0.01) and hypothyroidism (RR 1.90 [1.45, 2.55], p < 0.05; I2 = 85%, p < 0.01) during admission were associated with poor outcomes. Conclusion: Thyroid abnormalities increased the risk of COVID-19 composite poor outcomes and were influenced by the patient's age. Abnormal thyroid and hypothyroidism, but not hyperthyroidism, were associated with poor COVID-19 outcomes. Highlights: Thyroid disorders are associated with higher risks of COVID-19 composite poor outcomes. The association between thyroid disorders and COVID-19 poor outcomes varies with age. Unspecified thyroid abnormalities and hypothyroidism, but not hyperthyroidism are associated with COVID-19 poor outcomes.